2019
DOI: 10.1021/acs.langmuir.9b02558
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Viscous Oil-in-Water Nanoemulsions to Viscoelastic Gels upon Removal of Excess Ionic Emulsifier

Abstract: Viscous, flowable nanoemulsions stabilized with ionic emulsifier can be transformed into repulsively jammed elastic gels that do not flow under gravity by reducing the droplet size and increasing the interfacial repulsive shell layer thickness. However, a high concentration of emulsifier required to achieve nanodroplets could remain in the continuous phase and lead to oscillatory structural forces, thereby reducing repulsive interaction and forming flowable liquid systems. It was hypothesized that the removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Therefore, by increasing the chitosan concentration, the rheology of monolayer emulsion was transformed from a flowable liquid-like material to a self-supporting elastic gel due to droplet aggregation at 0.1 wt% and finally into a repulsive bilayer viscoelastic gel at 0.25 wt%. Moreover, comparing with our previous study, 10 where we obtained repulsive gelation in a 3 wt% Citrem stabilized monolayer 40 wt% O/W emulsion, in the present case, about 6-times increase in the gel strength was observed for the chitosan-coated bilayer emulsion gels at 36 wt% oil. Therefore, by changing the composition, a further Food & Function Paper decrease in the oil concentration of the bilayer emulsions would be possible while keeping the gel strength similar to the monolayer emulsions.…”
Section: Papersupporting
confidence: 85%
See 4 more Smart Citations
“…Therefore, by increasing the chitosan concentration, the rheology of monolayer emulsion was transformed from a flowable liquid-like material to a self-supporting elastic gel due to droplet aggregation at 0.1 wt% and finally into a repulsive bilayer viscoelastic gel at 0.25 wt%. Moreover, comparing with our previous study, 10 where we obtained repulsive gelation in a 3 wt% Citrem stabilized monolayer 40 wt% O/W emulsion, in the present case, about 6-times increase in the gel strength was observed for the chitosan-coated bilayer emulsion gels at 36 wt% oil. Therefore, by changing the composition, a further Food & Function Paper decrease in the oil concentration of the bilayer emulsions would be possible while keeping the gel strength similar to the monolayer emulsions.…”
Section: Papersupporting
confidence: 85%
“…It was found that two ultracentrifugation cycles were enough to remove almost all unabsorbed Citrem from the emulsion continuous phase. 10 The final Citrem-stabilized emulsion without excess emulsifier was adjusted to pH 4 using 1 N HCl. To prepare the bilayer emulsions, the second layer of positively charged chitosan with different degrees of deacetylation (DDA 93% and 50%) was deposited on Citremstabilized droplets according to Kaasgaard and Keller.…”
Section: Preparation Of Secondary Emulsionsmentioning
confidence: 99%
See 3 more Smart Citations